2020
DOI: 10.1021/acssuschemeng.0c05280
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Shear Strength of Fly Ash Powder Beds

Abstract: Control of the adhesion properties of fly ash represents a considerable challenge for the maintenance and operation of a wide range of combustion plants throughout the world. This is especially true for biomass combustion, which has seen growing interest as a renewable energy production source given that biomass usually contains a significant amount of chlorine, sulfur and alkali metals. These elements are known to cause severe fly ash adhesion in combustion plants and are also responsible for plant corrosion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…A device to evaluate the adhesiveness of particles at high temperatures was developed previously and could measure the adhesiveness of many types of particulate materials, including combustion and incineration ashes. An analysis of various ashes revealed that P, Na, and K in ashes increased adhesiveness at high temperatures. For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. , This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A device to evaluate the adhesiveness of particles at high temperatures was developed previously and could measure the adhesiveness of many types of particulate materials, including combustion and incineration ashes. An analysis of various ashes revealed that P, Na, and K in ashes increased adhesiveness at high temperatures. For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. , This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we also developed a shear strength tester, which can directly measure the shear strength of fly ash powder beds that are closely related to the surface adhesion (Figure 2). 39 Given the chemical complexity and diversity of fly ash samples collected from commercial thermal plants, it is more difficult to study the mechanistic aspects of deposition involving real fly ash samples; hence, a synthetic ash strategy was devised, whereby chemically synthesized inorganic particles may be used instead of real samples. In combination with the tensile strength tester, this strategy enabled us to better understand mechanistic aspects of the interparticle adhesion due to sodium and potassium.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have developed a tensile strength tester for powder beds under high-temperature conditions, which has allowed for the direct evaluation of adhesiveness in a powder bed . The tester was effectively used to analyze the adhesiveness of ash powder beds collected from commercial combustion plants at high temperatures. Furthermore, it was clarified that the addition of aluminum oxide (Al 2 O 3 ) nanoparticles to coal ash and sewage sludge ash could effectively suppress the increase in particle adhesiveness; these results could contribute to the realization of highly efficient energy recovery in combustion processes. However, the details of adhesiveness at high temperatures, especially the chemical composition of ashes, remain unclear, because the combustion ashes have complex chemical components and physical properties such as porosity, which also affect the tensile strength of powder beds. ,, We have developed a synthetic ash strategy that employs a synthetic ash synthesized from a stable base material such as silicon oxide (SiO 2 ) and a target element that has the potential to increase particle adhesiveness, such as Na and K (Figure ). This strategy is a powerful tool to understand the chemical effect on adhesiveness because synthetic ashes have almost uniform physical properties, and the chemical components are simple and controllable.…”
Section: Introductionmentioning
confidence: 99%